The sexual behaviours of adolescents aged between 14 and 17 years involved with the juvenile justice system in Australia: A community-based survey - Yap, L.; Jones, Jocelyn; Donovan, B.; Nathan, S.; Sullivan, E.; Davison, S.; Heffernan, E.; Richards, A.; Meurk, C.; Steele, M.; Fisher, C.; Ton, B.; et al. (2020)
© 2020 Yap et al. Objectives: To overcome key knowledge gaps in relation to justice involved and vulnerable young people and their sexual health and to compare this group with their peers from other youth health surveys in Australia to determine the extent of the issues. Methods: Young people, aged between 14 and 17 years, who had ever been or were currently involved with the criminal justice system were purposively sampled. The survey was anonymous and delivered using Computer Assisted Telephone Interview (CATI). Results: A total of 465 justice involved MeH-JOSH young people, aged between 14 and 17 years, participated in the study: 44% Aboriginal and/or Torres Strait Islander (Indigenous) and 37% not attending school. Of the total valid responses, 76% (n = 348) reported having ever had sex, with sexual initiation at a median age of 14 years. We compared these data with their peers in other Australian surveys and found that young people in our study had a higher engagement in sex and start having sex at a younger age, reporting more sexual partners at all ages. Conclusions The sexual behaviours of young people involved in the justice system in this study suggest they may be at a greater risk for sexually transmissible infections than their age-matched peers in the general population. Policymakers should elevate them to a priority population for targeting sexual health services and health promotion.